Contrasting breeding systems in six species of Tillandsia L. (Bromeliaceae) from woody areas of Santa Fe Province: Argentina - Bianchi, Marta Beatriz (2014)
The reproductive biology of six native Tillandsia species that co-occurred in woody areas of Santa Fe Province (Argentina) was studied for floral biology, breeding systems and reproductive success. Flower longevity, floral phases, hand self- and cross-pollinations or natural pollinations and fluorescence microscopy observations of post-pollination events were analysed. Also pollen/ovule (P/O) ratio and pre-emergent reproductive success (PERS) were compared between species. In T. ae¨ranthos, T. ixioides and T. meridionalis, self-pollinated flowers mostly failed to form fruits, and fluorescence microscopy studies showed that in selfed pistils pollen tube growth was arrested in the style. It is likely that these species have homomorphic, gametophytic self-incompatibility. In contrast, T. capillaris, T. tricholepis and T. recurvata regularly formed fruits following autonomous self-pollination. Floral traits, the P/O ratios and PERS indices correlate with the breeding systems found in these two groups of species: the three selfing species have inconspicuous closed flowers, and they have low P/O ratios and high PERS values. In contrast, the three self-incompatible (SI) species have conspicuous flowers with relatively high P/O and low PERS values. We described here three new cases of SI in Tillandsia species subgenera Anoplophytum and confirm the autogamous and cleistogamous status in three species of Tillandsia subgenera Diaphoranthema